2017
DOI: 10.1590/0103-8478cr20160974
|View full text |Cite
|
Sign up to set email alerts
|

Customer relationship management in the agricultural machinery market

Abstract: Customer Relationship Management can be regarded as a business approach. The objective was to know the customers, meet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Thus, delightful is not a consumer priority for small farmers; service that suit with farmers expectations is more critical (Leninkumar, 2019) and no more. This result supported by earlier study that showed customer satisfaction is a top priority for each work unit in agribusiness supply companies, including their salespeople (Nunes et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, delightful is not a consumer priority for small farmers; service that suit with farmers expectations is more critical (Leninkumar, 2019) and no more. This result supported by earlier study that showed customer satisfaction is a top priority for each work unit in agribusiness supply companies, including their salespeople (Nunes et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Loyal customers would be stay with companies over time and purchase more in greater quantity and higher frequency (Yang, 2011). Facing this situation, companies carry out various business strategies, such as improving service quality, to maintain customer loyalty (Nunes et al, 2017) such as enhancing product and service quality to over reward or delight their customer by achieving more than just satisfaction to influence repurchase behavior (Alexander, 2012).…”
Section: December 2022 491mentioning
confidence: 99%
See 1 more Smart Citation
“…Customer relationship in the agricultural machinery market found that electronicbased customer relationship management was superior to conventional customer management in boosting sales [26]. Furthermore, it is also stated that customer relationship management-complications and implementation in an organization revealed that customer relationship management applications have benefits in increasing product market share.…”
Section: Introductionmentioning
confidence: 99%